Schizophrenia-Like Psychotic Symptoms Associated to Leigh Syndrome - Jaballah, F.; Ben Soussia Nouira, R.; Mallouli, S.; Boussaid, H.; Younes, S.; Zarrouk, L.; Younes, S. (Case Reports in Psychiatry, 2023)
Introduction. Leigh syndrome (LS) is a mitochondrial disease characterized by subacute necrotizing encephalomyelopathy with an estimated incidence of 1:40,000 births. The comorbidity of psychotic symptoms noted in mitochondrial and psychiatric diseases has spurred interest in the effects of DNA mutations and psychiatric disorders. Case presentation. We report the case of a Tunisian 28-year-old male diagnosed with maternally inherited Leigh syndrome. He presented anxiety and auditory hallucinations, and he reported a vague, unsystematized delusion evolving since 6 months. Significant remission was observed at risperidone 3 mg/day. Discussion. The normality of explorations in our case raised the issue of the link between the two diseases, supporting the hypothesis that mitochondrial dysfunction maybe the primary origin of psychotic disorders. Conclusion. The aim of our work is to study the relations between mitochondrial dysfunction and psychiatric symptoms. Further study of mitochondrial dysfunction in psychiatric disorders is expected to be useful for the development of cellular disease markers and new psychotropics.